Study of Structural Properties of Ni3Pb2S2 Films - Ho, Soon Min (2017)
In this work, X-ray diffraction technique was applied to determine the structure of nickel lead sulphide thin films prepared by chemical bath deposition. The X-ray diffraction patterns reflect that polycrystalline Ni3Pb2S2 could be obtained using the method explained. The XRD data show that an increasing the deposition time from 7 to 30 hours resulted in increase in the number of peaks.